Survey Perilaku Hidup Bersih Dan Sehat (PHBS) Siswa SMP Negeri 1 Pakisjaya - Khoirullah; Setio Nugroho; Rolly Afrinaldi; Deden Akbar Izzuddin (Universitas Singaperbangsa, 2021)
The problem that becomes the reference in this research is How big is the Clean and Healthy Life Behavior (PHBS) of students of SMPN 1 Pakisjaya? Based on the above problems, the purpose of this study is to determine the Clean and Healthy Life Behavior (PHBS) of students of SMPN 1 Pakisjaya. This study used a survey method with a descriptive quantitative approach. There is a sampling using random sampling technique, with a total sample of 83 students at Pakisjaya State Junior High School. The data collection tool to measure Clean and Healthy Behavior (PHBS) uses a Clean and Healthy Life Behavior Questionnaire (PHBS). From the results of this study, it is known that the Clean and Healthy Behavior of SMP Negeri 1 Pakisjaya students stated that they were in the